Development of Flipped Classroom-Based Interactive Multimedia to Enhance Learning Independence in Physics Education - Wahyuni, Ida; Megalina, Yeni; Tanjung, Ratna; Sihombing, Rizky Agassy (Universitas Negeri Semarang, 2025)
Many prospective physics teachers struggle with innovative instructional strategies, as seen in their inability to answer examiners’ questions during thesis defences. This study focuses on the course Development of Physics Teaching Programs and aims to develop interactive multimedia based on the flipped classroom model using I-Spring Suite 10 to enhance students’ learning independence. The research was conducted in the Physics Department of Universitas Negeri Medan using the ADDIE model. The developed multimedia combines theoretical materials, interactive features, and classroom simulation videos to support an engaging learning experience. Expert validation showed that the product is appropriate for instructional use. After implementation, students demonstrated improved independence and confidence in applying teaching strategies. The effectiveness test using the N-Gain formula showed a medium level of improvement. These results indicate that the multimedia is reasonably effective in helping prospective physics teachers understand and apply instructional strategies in both theoretical and practical teaching contexts.